55‐3: Invited Paper: Flexible Hybrid Electronics Using Display Infrastructure. Issue 1 (28th June 2021) - Lee, Cheng-Chung; Chiu, Steve; Lai, Hsin-Cheng; Wang, Terry; Cheng, Shau-Fei; Yang, Frank; Chen, Heng-Yin
Abstract : Flexible and stretchable circuit is the key element for the upcoming flexible hybrid electronics in addition to high performance silicon based active devices and passive components. The circuitry and structure design of the circuit carrier have to be able to withstand the stress and tolerate biometric signal variation induced by external force. These circuit carriers can be fabricated by use of the flexible display technologies and facilities. In this study, we integrated ICs, passive components and sensors to form a system upon flexible/plastic circuit carrier. Bendable and/or stretchable smart textiles and patches were successful demonstrated with the functionality of electromyography (EMG) and electrocardiography (ECG).